Regional assessment of the seagrass halodule beaudettei - (den hartog) den hartog in the tropical Atlantic Seagrass Bioregion (Bioregion 2) for the IUCN red list - Creed, Joel Christopher (2025)
The current taxonomic status is unclear. The taxonomic validity of this species has been questioned, and it has been suggested as a synonym of Halodule wrightii (Eiseman, 1980; Rivera-Guzmán et al. 2016; Wheeler et al. 2020). Its species status is based on leaf- tip morphology which is highly variable (den Hartog, 1964; Larkum et al. 2006). According to Rivera-Guzmán et al (2016) in the United States H. beaudettei has been traditionally referred to as H. wrightii.. Taxonomic uncertainty will remain until phylogeographic studies that combine re-examination of type material, descriptions of leaf tip morphology and genetic analyses are conducted over sufficiently broad (i.e., range wide) spatial scales